Dubious deeds : Book one of the further advenrures of Eddie Dickens - Ardagh, Philip; Roberts, David (London : Faber and faber, 2003)
Eddie Dickens finds himself far from home in the heathery highlands of Scotland for some Further Adventures embracing a whole host of new characters and firm favourites such as Malcolm the stuffed stoat. Including Dubious Deeds, Horrendous Habits and The Final Curtain, fans of Philip Ardagh will gobble up this great gift edition.
Keywords: Young Adult book -- children's fiction